Handbook of algal technologies and phytochemicals - Ravishankar, Gokare A.; Ambati, Ranga Rao (Boca Raton : CRC Press, 2020)
Key features: The most comprehensive resource available on the biodiversity of algal species, their industrial production processes and their use for human consumption in food, health and varied applications. Emphasis on basic and applied research, addressing aspects of scale-up for commercial exploitation for the development of novel phytochemicals (phytochemicals from algae). Addresses the underexplored and underutilized potential of chemicals from marine sources for health benefits. Each chapter, written by expert contributors from around the world, includes Summary Points, Figures and Tables, as well as up-to-date references. The first book in this two-volume set explores the diversity of algal constituents for health and disease applications. The commercial value of chemicals of value to food and health is about $6 billion annually, of which 30 percent relates to micro and macro algal metabolites and products for health food applications. This comprenhensive volume looks in detail at algal genomics and metabolomics as well as mass production of microalgae. As a whole, the two-volume set covers all micro and macro algal forms and their traditional uses; their constituents which are of value for food, feed, specialty chemicals, bioactive compounds for novel applications, and bioenergy molecules. Bio-business and the market share of algae-based products are also dealt with, providing global perspectives.
Volume I: food, health and nutraceutical applications
OCLC-licensed vendor bibliographic record.
Keywords: Algae products; Algae -- Biotechnology; SCIENCE / Life Sciences / General; SCIENCE / Life Sciences / Biology / Marine Biology; MEDICAL / Biotechnology